Riding the creative roller coaster: How leadership evoke creativity Productivity and innovation - Nick Udall (KoganPage, 2014)
"Leadership is about creating opportunities for individuals and teams in order to cultivate innovation at all levels of an organization. The only way to shape purposeful, meaningful and successful futures is through innovation. This book turns the current understanding of innovation on its head. It explores how innovation is actually a mindset, not a business led process. How we think, relate, learn and organize